(untitled) (Ameghiniana, 2013)
A small Early Jurassic Flora is clescribecl in this paper. It inclucles 18 ídentifiable species, they are: Neocalamites carrerei (Zeil!.) Halle, Marattia munsteri Goeppert Gleichenites sp., Goeppertella cf. memoria-watanabei Oishi et Huzíoka, Otozamites albosaxatilis Herbst, O. ameghinoi Kurtz, O. bechei Brongniart, O. hislopi (Olclham) Feist., Ptilophqllum.acutijolium. Morris, Araucarites phillipsi Carruthers, Elatocladus conferta (Old. & Hlorr.) Halle, Cladophlebis mendozaensis (Gein.) Fr., C. oblonga Halle, Kurtziana brandmayri Fr., K. cacheutensis Fr., Scleropteris vincei Herbst, Taeniopteris sp. The flora is typicaJly Liassic and is probably I-Iettangian in age.